Implementation of Message Service Queue Using Rabbit MQ - Kumar, Deepti Ravi; Kishore, Nandha; Raj, D. Rahul; Raswanth, E. A.; Sreekanth, Samyuktha; Sruthi, S.; Anusha, T. (Journal of Electronics and Informatics, 2023)
A distributed system is a software application that makes use of a collection of protocols to manage the activities of numerous processes running on a communication network, so that each part cooperates to finish a single or a condensed number of related tasks. Representational State Transfer (REST) API is also integrated into this, making it simple to access online services without the need for additional processing. The server sends a client-side representation of the requested resource whenever a RESTful API is used. It is also integrated with microservices through the open-source message-broker programme RabbitMQ. With little developer involvement, the configuration file must automatically network new messaging services that join the distributed system.